User Acceptance Test For Digital Signature Application In Academic Domain To Support The Covid-19 Work From Home Program - Irawan Afrianto; Andri Heryandi; Alif Finandhita; Sufa Atin (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
The user acceptance test (UAT) is the final stage in the production of the application. This is intended to see the degree to which the system can function and satisfy the needs of its users. The objectives of this research is to test the function and user acceptance of the digital signature application in the academic environment to support the covid-19 work from home program. The approach used in the user acceptance test is to use the black box method and the Likert scale questionnaire to figure out the functional scope of the program, as well as the acceptance of system by users while using the application. The results of the test show that the digital signature application that has been designed, functionally can run well and generates a user acceptance value of 82.07%. It can be concluded that the application that was developed has been accepted by users and fulfills the needs of its users, it is an alternative solution, especially in signing academic documents during the current Covid-19 pandemic.